Agribusiness competitiveness: Applying analytics, typology, and measurements to Africa - Babu, Suresh Chandra; Shishodia, Mahika (International Food Policy Research Institute, 2017)
Agribusiness has a major role to play in the transformation of the agricultural sector in Africa. With the demand for high-value food products increasing around the world, the production and export of these goods represents an opportunity to achieve increases in income and employment. To capture the benefits of this trend and capitalize on this opportunity for long-term agricultural growth, agribusiness in Africa must become more competitive. In addition to improving competitiveness, increasing agricultural productivity and food security are also major challenges in African agricultural development. In this paper, we compare the agribusiness competitiveness of African countries and develop typologies connected with their food security and agricultural productivity status. The typologies reveal various stylized facts on the competitiveness of agribusiness to help nations prioritize issues for agricultural development and growth. We develop the measures of agribusiness competitiveness and apply them to African countries. Additionally, we present policy implications and lessons for increasing the competitiveness of agribusiness in African countries.